Young Children Selectively Expect Failure Disclosure to High‐achieving Peers. Issue 2 (28th April 2016) - Hicks, Catherine M.; Liu, David
Abstract : Children make many decisions about whether and how to disclose their performance to peers, teachers, parents and others. Previous research has found that children's disclosure declines with age and that older children and teenagers preferentially choose a peer audience for performance disclosure based on similar achievement. This research examines younger children's choice of a disclosure audience: whether young children predict that people will distinguish between peers at different achievement levels, and whether or not younger children expect preferential selections between those peers for their performance disclosure. One hundred and thirty‐nine children, aged 3 to 6 years, were asked about a character's disclosure of classroom performance information. At least until the age of 6 years, children predicted significantly greater disclosure of failure to a high achieving peer who had been successful. When asked to predict the disclosure of success, however, children in all age groups did not discriminate between disclosing to the high‐achieving or low‐achieving peer. This evidence suggests that very young children may not show the same valence‐matching preferences as older children and that early school ages are a critical time when children begin to adopt social norms around disclosure that impinge on possible help‐seeking. Copyright © 2016 John Wiley & Sons, Ltd.